The association between cervical lordosis and age, sex, history of cervical trauma and sedentarity: A CT study - David Ezra; Leonid Kalichman; Azaria Simonovich; Jonathan Droujin; Ella Been And Deborah Alperovitch-Najenson (Archives of Anatomy and Physiology - Peertechz Publications, 2020)
Purpose: We evaluated the association between cervical lordosis and age, sex, sedentarity, and history of cervical trauma.  Methods: CT scans of 206 individuals, 111 with and 95 without a history of cervical trauma were divided into three age groups (18-39, 40-59 and 60+ years). The cervical lordosis measurements [C0-C7 (total), C0-C3 (upper), C2-C7 (mid-lower), and C3-C7 (lower)] were obtained from CT scans using the Cobb method.  Results: A history of cervical trauma was associated with total and mid-lower cervical lordosis, indicating a reduction of the lordosis compared to the group with no history of cervical trauma. Significant sex differences in the non-trauma group were found only in the young (20-39) and intermediate (40-59) age groups with males exhibiting greater lordosis angles than females. Older females, without a history of cervical trauma, had greater mid-lower and lower cervical lordosis than younger females. Sedentary work predicted the magnitude of the upper cervical lordosis. Subjects working in a sedentary position develop forward head posture, which may eventually advance to head and neck pain.  Conclusion: A history of cervical trauma leads to a reduction of the lordosis. The relationship between history of cervical trauma and cervical lordosis needs to be further investigated vis-à-vis the clinical causes and outcomes. Moreover, prevention strategies should be available to sedentary workers in order to maintain proper lower cervical lordosis and prevention of upper cervical lordosis exaggeration.